Evaluating the Performance of Spatial Indicators of Destination Accessibility for Physical Activity Research: A Comparative International Analysis - Cerin, E; Adams, MA; Conway, TL; Frank, LD; Cain, KL; Lai, PC; Duncan, S; Queralt, A; Timperio, A; Schipperijn, J; Reis, RS; Van Dyck, D; et al. (Elsevier BV, 2025)
Neighbourhoods with good access to various destinations facilitate engagement in physical activity. Because spatial indicators of destination accessibility can be operationalised in numerous ways, it is important to evaluate their ability to explain physical activity in various geographical and cultural contexts. We evaluated established as well as novel spatial indicators of destination accessibility using data from 12 cities/regions participating in an international study on adolescents' physical activity. Twelve spatial indicators of destination accessibility were developed using land use data. Five indicators represented measures of destination intensity (density), two were indicators of destination heterogeneity [land use mix (LUM) indices], and the remaining five were novel measures of combined destination intensity and heterogeneity. To evaluate these spatial indicators, we examined their performance as correlates of parent-perceived destination accessibility and adolescents' physical activity, and the extent to which the findings were generalisable across cities/regions. Substantial differences in ability to explain physical activity and comparability across geographical locations were observed across the indicators. The best performing indicator, defined as being a consistent correlate of parental perceptions of destination accessibility and adolescents' physical activity in the expected direction and across cities/regions, was a novel hybrid intensity + heterogeneity indicator: gross density of non-residential destinations weighted by a novel parcel-count-based LUM index. Indicators based on ratios of non-residential land/parcels to residential land/dwelling units performed poorly on most criteria, while LUM indices performed well in relation to transport-related physical activity. We provide recommendations regarding the usage of spatial destination accessibility indicators in physical activity research.
Keywords: 4406 Human Geography; 44 Human Society; Minority Health; Prevention; 15 Life on Land; 1205 Urban and Regional Planning; 1604 Human Geography; Urban & Regional Planning; 3304 Urban and regional planning; 4406 Human geography; 4407 Policy and administration